Advanced lung cancer inflammation index is associated with long-term cardiovascular death in hypertensive patients: national health and nutrition examination study, 1999–2018 - Tu, Jiabin; Wu, Bo; Xiu, Jiaming; Deng, Jiayi; Lin, Shuqiong; Lu, Jin; Yan, Yanfang; Yu, Pei; Zhu, Jinlong; Chen, Kaihong; Ding, Shan; Chen, Liling (Frontiers in Physiology, 2023)
Background: Hypertension is one of the main causes of cardiovascular death. Inflammation was considered influential factors of cardiovascular (CVD) death in patients with hypertension. Advanced lung cancer inflammation index (ALI) is an index to assess inflammation, few studies have investigated the relationship between advanced lung cancer inflammation index and cardiovascular death in hypertensive patients. Objective: The aim of this study was to investigate the association between advanced lung cancer inflammation index and long-term cardiovascular death in hypertensive patients. Method: Data from the National Health and Nutrition Examination Survey (NHANES) 1999–2018 with mortality follow-up through 31 December 2019 were analyzed. Advanced lung cancer inflammation index was calculated as BMI (kg/㎡) × serum albumin level (g/dL)/neutrophil to lymphocyte ratio (NLR). A total of 20,517 participants were evaluated. Patients were divided into three groups based on tertiles of advanced lung cancer inflammation index as follows: T1 (n = 6,839), T2 (n = 6,839), and T3 (n = 6,839) groups. The relationship between advanced lung cancer inflammation index and long-term cardiovascular death was assessed by survival curves and Cox regression analysis based on the NHANES recommended weights. Results: The median advanced lung cancer inflammation index value in this study was 61.9 [44.4, 84.6]. After full adjustment, the T2 group (hazard ratio [HR]: 0.59, 95% confidence interval [CI]: 0.50–0.69; p < 0.001) and T3 group (HR: 0.48, 95% CI: 0.39–0.58; p < 0.001) were found to have a significantly lower risk of cardiovascular death compared to the T1 group. Conclusion: High levels of advanced lung cancer inflammation index were associated with reduced risk of cardiovascular death in hypertensive patients.